PENERAPAN PERPAJAKAN PADA DANA DESA DI DESA ANJIR SERAPAT TENGAH KABUPATEN KAPUAS KALIMANTAN TENGAH TAHUN 2021 - Khairani Safitri; Saprudin (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2022)
This study aims to determine the tax application system on the use of Village Funds, the amount of village funds received in 2021, taxes imposed on village funds, as well as procedures for collecting and calculating taxes on village funds. This research begins by finding out the total village funds received, then finding out the taxes applied, and finally calculating the taxes imposed on village funds in 2021. The results of the study found that the 2021 village fund was Rp. 1,421,453,000, Tax paid Rp. 22,320,877, the types of taxes imposed are PPH Article 22, PPH Article 23, VAT, and Excavation Tax C.